Volume 4: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1999
DOI: 10.1115/99-gt-020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Coefficients of Stepped Labyrinth Gas Seals

Abstract: Rotor-fluid interactions can cause self-excited shaft vibrations of high density turbomachinery. Often the amplitude of the vibrations reaches unacceptably high amplitudes and the scheduled power or running speed cannot be achieved. One of the most important sources of excitation is the flow through labyrinth seals. For a reliable design it is necessary to predict these forces exactly, including not only stiffness but also damping coefficients. As the forces in labyrinth gas seals are rather sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recently, various seal geometries, e.g., stepped labyrinth seal and honeycomb seal, were numerically investigated by Kleynhans [8], Yucel and Kazakia [9] and Dursun [10]. Cross-coupled stiffness coefficients of stepped labyrinth seal predicted by Yucel [11] showed relatively good agreement with the experimental data [12]. Further more, a set of differential equations were employed to allow the clear flow structure of the leakage air flow through a straight-labyrinth seal [13,14].…”
Section: Introductionmentioning
confidence: 96%
“…Recently, various seal geometries, e.g., stepped labyrinth seal and honeycomb seal, were numerically investigated by Kleynhans [8], Yucel and Kazakia [9] and Dursun [10]. Cross-coupled stiffness coefficients of stepped labyrinth seal predicted by Yucel [11] showed relatively good agreement with the experimental data [12]. Further more, a set of differential equations were employed to allow the clear flow structure of the leakage air flow through a straight-labyrinth seal [13,14].…”
Section: Introductionmentioning
confidence: 96%
“…The presence of rub grooves would deteriorate the sealing performance or even induce the seal failure. Previous studies [2][3][4] have shown that leakage flow through labyrinth seals without rub grooves would give a significant influence on the rotor dynamics. Accordingly, an insight understanding of influence of rub grooves on dynamics of the rotor subjected to aerodynamic forcing of the leakage flow is of essential significance.…”
Section: Introductionmentioning
confidence: 99%